Anaesthetic efficacy of lidocaine and articaine in inferior alveolar nerve block combined with buccal infiltration in patients with irreversible pulpitis - Shrimanikandan Ayappa Gandhi; Sambarta Das; Abhisek Das; Yoshaskam Agnihotri; Rajanna Venkatraman Mohan; Venkata Ramanan Dasu Subramanian (Wolters Kluwer Medknow Publications, 2021)
Purpose: This prospective, randomized, double-blinded study was conducted to compare the anesthetic efficacy of 2% lidocaine with 1:200,000 epinephrine and 4% articaine with 1:200,000 epinephrine in inferior alveolar nerve block (IANB) combined with buccal infiltration in patients with irreversible pulpitis. Methods: Group I: Thirty patients received IANB of 2% lidocaine without buccal infiltration. Group II: Thirty patients received IANB of 2% lidocaine followed by buccal infiltration with 2% lidocaine. Group III: Thirty patients received IANB with 4% articaine followed by buccal infiltration with 4% articaine. Pain during the procedures was recorded by using a Heft Parker visual analog scale. No pain or mild pain on endodontic access was recorded as success and analyzed using Chi-square analysis. Results: Group I obtained 30% success rate. Fifty percent successful anesthesia was obtained for Group II. The success rate was increased to 70% for Group III with statistically significant difference among all the groups (P < 0.05). Conclusion: The use of 4% articaine as both IANB and buccal infiltration recorded the highest success rate (70%) when compared to either 2% lidocaine as IANB with buccal infiltration (50%) or 2% lidocaine as IANB alone (30%) in patients with irreversible pulpitis.